2001
DOI: 10.1093/clinchem/47.6.1008
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Prevalence of Antibodies to β2-Glycoprotein I, Prothrombin, Protein C, Protein S, and Annexin V in Patients with Systemic Lupus Erythematosus and Thrombotic and Thrombocytopenic Complications

Abstract: Background: Anti-phospholipid (aPL) antibodies (Abs) frequently found in the plasma of patients with systemic lupus erythematosus (SLE) have been associated with thrombotic complications. Our aim was to clarify the roles in thrombosis of aPL Abs that react with complexes of phospholipids and plasma proteins such as β2-glycoprotein I (β2-GPI), prothrombin, protein C, protein S, and annexin V. Methods: We determined the prevalence of aPL Abs to various phospholipid-binding plasma proteins in SLE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 41 publications
1
62
0
2
Order By: Relevance
“…In another report, both IgG and IgM anti-b2GP1 correlated with venous thrombosis, but only IgM anti-b2GP1 correlated with arterial thrombosis (Horbach et al, 1996), which is consistent with our findings. Both anti-b2GP1 and anti-CL IgG were found to be significantly related to arterial and venous thrombosis in a study that did not assess IgM (Nojima et al, 2001). This study revealed that anti-CL IgG and anti-b2GP1 IgG were both stronger and more frequent in arterial than in venous thrombosis, which is discordant with our findings.…”
Section: Anti-b2gp1supporting
confidence: 63%
“…In another report, both IgG and IgM anti-b2GP1 correlated with venous thrombosis, but only IgM anti-b2GP1 correlated with arterial thrombosis (Horbach et al, 1996), which is consistent with our findings. Both anti-b2GP1 and anti-CL IgG were found to be significantly related to arterial and venous thrombosis in a study that did not assess IgM (Nojima et al, 2001). This study revealed that anti-CL IgG and anti-b2GP1 IgG were both stronger and more frequent in arterial than in venous thrombosis, which is discordant with our findings.…”
Section: Anti-b2gp1supporting
confidence: 63%
“…26 The association between miscarriage and anti-AnxV antibodies has already been described in numerous retrospective studies, in women with recurrent miscarriages 14,15,27 and in women with systemic lupus erythematosus. 13,28,29 In an earlier study, we found that anti-AnxV antibodies were present in 17% of subjects with recurrent miscarriage and were the only immunological marker among aCL, antiβ 2 GPI, and antiprothrombin, which was correlated with the occurrence of miscarriage, though to a moderate extent (P = .02). 17 Conversely, Arnold et al observed the presence of anti-AnxV antibodies in 35% of aCL-positive women with miscarriage and 19% of aCL-negative women, but did not find that anti-AnxV constituted a risk factor for miscarriage; 30 equally, Ogawa et al found no correlation between AnxV and miscarriage in patients with APS.…”
Section: Discussionmentioning
confidence: 86%
“…12 However, in addition to aCL and LAC, other antiphospholipid antibodies or antiphospholipid-binding proteins are probably involved, including anti-annexin V (AnxV) antibodies, which numerous retrospective studies have found to be associated with a higher frequency of occasional and recurrent miscarriages. [13][14][15] Annexin V is a glycoprotein with natural anticoagulant activity and a high affinity for anionic phospholipids; it is expressed by trophoblasts and endothelial cells, and its anticoagulant activity is associated with its ability to act competitively with coagulation factors for the phospholipid-binding sites, preventing their activation. Anti-AnxV monoclonal antibodies have proved able to divert annexin V from the surface of the trophoblast cells, thus promoting a procoagulant effect.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors can alter the measured frequency of APLA-positive patients in ITP, such as the number of target antigens tested. In addition to the six antigens tested in our study, many other protein cofactors of APLA are recognized, such as prothrombin, protein C, protein S, annexin V and others cited in reviews (Schultz, 1997;Galli & Barbui, 1999;Donohoe et al, 2001;Nojima et al, 2001;Arnout & Vermylen, 2003;Galli et al, 2003a), or currently unidentified. Accordingly, the measured incidence of APLA in ITP would be expected to be even higher if those other antigens were also tested.…”
Section: Discussionmentioning
confidence: 94%